Diagnostic utility of BINAX NOW RSV - an evaluation of the diagnostic performance of BINAX NOW RSV in comparison with cell culture and direct immunofluorescence - Jonathan Nteimam (BMC, 2006)
Abstract Background The regular increase in the incidence of respiratory illness caused by respiratory syncytial virus (RSV) during winter months in the United Kingdom, and other countries with temperate climate is usually accompanied by increased bed pressures especially in paediatric units in these countries. As a result, there is usually an increase in the demand for infection control services during these months. This makes obvious the need for making a rapid diagnosis of the infection during these months. BINAX NOW RSV (Maine, USA), a rapid membrane based immunochromatographic assay was designed to achieve this objective. Methods This study evaluated the diagnostic performance of BINAX NOW RSV in comparison with the methods routinely used in our laboratory namely direct immunofluorescence (DIF) and cell culture. Results and conclusion Results indicate that Binax Now RSV could be relied on to make infection control decisions in paediatric units during periods of peak RSV activity.